A Bio-Informatics Model for Task assignment and Fault Removal in Cloud Architecture - Dwivedi, Umesh; Dev, Harsh (International Journal of Psychosocial Rehabilitation, 2020)
Cloud computing is an emerging field and currently is being used in almost all the economical and manufacturing fields. Main reason of attraction towards this field is its number of attractive and beneficial features. Cloud architecture is designed in a fashion, that it can execute the tasks provided by the client in minimum time, minimum cost and without any fault. These assigned tasks need some resources for their execution. These resources are to be provided by the data centrers with help of virtual machines available there. Proper assignment of virtual machines to each task is very difficult. If this is not done properly, there is huge wastage of resources. Number of tasks are left unexecuted just because they are not getting their required resources or they have to wait for much longer time. Even if virtual machines get assigned to the tasks, there is no guarantee of proper resource assignment. Either resources are provided in bulk or there is a scarcity of resources for the task. It is also an arduous process. This paper uses two biotechnology algorithms named FASTA and BLAST for handling this proper resource assignment problem. These algorithms work in biological field for DNA mapping. They promptly map the complete strip in parallel. This paper uses these biological algorithms for resource assignments for the tasks to be executed. This paper explains about these biological algorithms and how they are nifty in resource assignment problem and its solution in very less amount of time. Finally, error occurring conditions which may arise while approximation adoption of result are explained and solved in detail.